2008
DOI: 10.1152/ajplung.00107.2007
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin enhances the barrier function of rat microvascular endothelium in a PAR-1-dependent manner

Abstract: Troyanovsky B, Alvarez DF, King JA, Schaphorst KL. Thrombin enhances the barrier function of rat microvascular endothelium in a PAR-1-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
2
13
1
Order By: Relevance
“…Interestingly, endothelial responses to thrombin exhibit a segment-specific heterogeneity in the pulmonary circulation, e.g., barrier disruption in conduit vessels vs. barrier enhancement in alveolar capillaries (43). In the present study, we demonstrated that P-selectin surface expression is stimulated by thrombin in both extra-alveolar vessel and alveolar capillary endothelium.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, endothelial responses to thrombin exhibit a segment-specific heterogeneity in the pulmonary circulation, e.g., barrier disruption in conduit vessels vs. barrier enhancement in alveolar capillaries (43). In the present study, we demonstrated that P-selectin surface expression is stimulated by thrombin in both extra-alveolar vessel and alveolar capillary endothelium.…”
Section: Discussionsupporting
confidence: 61%
“…As might be expected in this case, ligation of toll-like receptor 4 by LPS plays a key role in initiation of endothelial hyperpermeability in endotoxinmediated barrier injury (130). In addition, other upstream receptors have been shown to be involved in barrier regulation; thrombin increased EC permeability in EC monolayers (315) and increased macrovascular (but not microvascular) EC permeability in isolated, perfused rat lungs (636).…”
Section: Signals Leading To Initiation Of Barrier Disruptionmentioning
confidence: 62%
“…There have been attempts to measure changes in filtration coefficient in isolated lungs in response to thrombin perfusion [46,47,48]. However, the K F,C is expressed in relation to capillary pressure which therefore must stay constant during the measurement [49,50].…”
Section: Platelet-activating Factor (Paf)mentioning
confidence: 99%